Nursing Practices in Dementia Management and Care in Nepal - Pathak, Krishna Prasad (KMC Research Journal, 2019)
Nurses fell barriers in management and care of dementia patients. A purposive random sampling approach identified 44 Registered Nurses (RN). The Knowledge of RNs’ with regard to the diagnosis, management and care of dementia was unsatisfactory on the aspects of practices and management barriers are presented with regard to the following issues: negative views of dementia, difficulty in diagnosing early stage dementia, acceptability of specialists and responsibility for extra issues, knowledge of dementias and ageing, less awareness of declining abilities and diminished resources to handle care, guidelines, awareness of epidemiology and advice giving, and communicating the diagnosis.The following paper outlines the problems and solutions that Nepalese nurses’ in the community need to adopt in order to deal effectively with its diagnosis, care and management.